2005
DOI: 10.1111/j.1365-2664.2005.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Early impacts of forest restoration treatments on the ectomycorrhizal fungal community and fine root biomass in a mixed conifer forest

Abstract: 1.The obligate symbiosis formed between ectomycorrhizal fungi (EMF) and roots of tree species in the Pinaceae influences nutrient uptake and surrounding soil structure. Understanding how EMF respond to prescribed fire and thinning will assist forest managers in selecting fuel-reducing restoration treatments that maintain critical soil processes and site productivity. 2. The response of EMF species richness, live fine root biomass and duff levels to various forms and combinations of thinning and burning was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 65 publications
2
44
1
1
Order By: Relevance
“…The postfire changes in vegetation may more strongly shape the soil microbial community that represents the direct effects of the fire disturbance (71). Previous studies have reported that the loss of host plants after fire clearly reduces mycorrhizal fungal diversity (17,72). Our sites were dominated by P. sylvestris and included an abundant ericaceous understory, which can host both ECM and ERM fungi (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postfire changes in vegetation may more strongly shape the soil microbial community that represents the direct effects of the fire disturbance (71). Previous studies have reported that the loss of host plants after fire clearly reduces mycorrhizal fungal diversity (17,72). Our sites were dominated by P. sylvestris and included an abundant ericaceous understory, which can host both ECM and ERM fungi (73).…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of fungal biomass has been reported to be related to a decrease in SOM turnover time in a boreal fire chronosequence (14). Previous studies have shown that the increase in soil pH after fire favors bacteria (15) and reduces the richness and diversity of mycorrhizal fungi (16,17). Fire can also lead to significant losses in fungal biomass in organic horizons (18).…”
mentioning
confidence: 99%
“…Varied responses of ECM communities to fire have been described, with some studies finding postfire decreases in ECM biomass/diversity on Scots pine (Dahlberg et al 2001 ) and ponderosa pine stands (Stendell et al 1999; Smith et al 2005 in Sweden, California, and Oregon, respectively. Other studies have found fire altered ECM community structure in Douglasfir (Kennedy and Egger 2010 ), ponderosa pine (Gundale et al 2005 ), and spruce (Mah et al 2001 ) forests, without necessarily causing large changes in diversity or biomass, while a study on Scots pine forests in Sweden did not find any consistent change in ECM richness or composition following wildfire (Jonsson et al 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fire has been demonstrated to alter the community structure of both soil fungi (Cairney and Bastias 2007 ) and ECM fungi (Stendell et al 1999; Mah et al 2001; Dahlberg et al 2001; Smith et al 2005; Gundale et al 2005; Rincón and Pueyo 2010; Kennedy and Egger 2010; Buscardo et al 2012; Barker et al 2013). In addition, disturbance by MPB has been documented to increase fire severity (Turner et al 1999; Page et al 2012, with MPBattacked (red) stands experiencing higher severities of crown fire than might otherwise be expected (S. Taylor, CFS Forestry Officer, pers.…”
Section: Introductionmentioning
confidence: 99%
“…After a forest fire, the extent of the decrease in species richness (Smith et al, 2005, Hernández-Rodríguez et al, 2013 and relative abundance (Jonsson et al, 1999) and its further impact on forest regeneration depend on many factors such as variations in the intensity/severity of the fire, time elapsed after fire, the fire return interval and soil depth , Turrión et al, 2012. However, while the direct effect of fire is mainly destructive for existing fungal communities, at the same time fire also provides large inputs to new communities, mainly competition-free resources and substrates for fungi and plants to use (Penttilä & Kotiranta, 1996).…”
Section: Introductionmentioning
confidence: 99%